Conditional Inactivation of HIF-1 Using Intrabodies - Arjan J. Groot; Eelke H. Gort; Elsken van der Wall; Paul J. van Diest; Marc Vooijs (Cellular Oncology)
Hypoxia is a hallmark of solid cancers and triggers the transcription of genes responsible for cell survival. The transcription factor Hypoxia-Inducible Factor 1 (HIF-1) is a key regulator in this response and frequently activated in human cancer. HIF-1 activation is associated with tumor aggressiveness and poor clinical outcome and, therefore, may provide an attractive therapeutic target. Here we provide a novel approach for HIF-1 targeted therapy using single-domain llama antibodies directed against the HIF-1α oxygen dependent degradation domain which encompass the N-terminal transactivation domain. Conditional expression of HIF intrabodies in mammalian cells interfered with binding to pVHL and inhibited hypoxia induced activation of endogenous target genes. Inducible intrabody targeting is a highly specific strategy for temporal protein inactivation and may have applications for disease treatment.